Contemporary military theory : the dynamics of war - Angstrom, Jan; Widen, Jerker (London ; New York : Routledge/Taylor & Francis Group, 2015)
The book aims to provide the reader with a state-of-the-art introduction to classic and modern military theory. The text accounts for the most important theories within the field by developing and analyzing these theories, as well as problematizing both their normative and explanatory aims. While focusing on military theory, the book does not only reflect a single way of relating to knowledge of war and warfare, but furthers learning by introducing contrasting perspectives as well as constantly criticizing the theories. There is a clear need for an introductory text for the entire field of military theory that focuses whole-heartedly on the theories - not on their context or how they are expressed in practice during war. This book covers such questions as how we should understand the changing character of war, the utility of force and how the pursuit of political ends is achieved through military means. It draws upon and illustrates military thought through a wide-ranging number of examples from the Napoleonic Wars to the current war in Afghanistan. This book will be of great interest for students of military theory, strategic studies, security studies and defence studies.
Military theory: an introduction -- War -- Strategy -- The principles of war -- Joint operations -- Land operations -- Sea operations -- Air operations -- The dynamics of war: some conclusions.
Includes bibliographical references (pages 179-201) and index.
Keywords: Krieg; Military art and science; War (Philosophy); War; Military Science; Armed Conflicts; Military art and science; War; War (Philosophy); Military art and science; War (Philosophy); War